Optogenetic modulation of guanine nucleotide exchange factors of Ras superfamily proteins directly controls cell shape and movement - Pal, Dhiman Sankar; Lin, Yiyan; Zhan, Huiwang; Banerjee, Tatsat; Kuhn, Jonathan; Providence, Stephenie; Devreotes, Peter N. (Frontiers in Cell and Developmental Biology, 2023)
In this article, we provide detailed protocols on using optogenetic dimerizers to acutely perturb activities of guanine nucleotide exchange factors (GEFs) specific to Ras, Rac or Rho small GTPases of the migratory networks in various mammalian and amoeba cell lines. These GEFs are crucial components of signal transduction networks which link upstream G-protein coupled receptors to downstream cytoskeletal components and help cells migrate through their dynamic microenvironment. Conventional approaches to perturb and examine these signaling and cytoskeletal networks, such as gene knockout or overexpression, are protracted which allows networks to readjust through gene expression changes. Moreover, these tools lack spatial resolution to probe the effects of local network activations. To overcome these challenges, blue light-inducible cryptochrome- and LOV domain-based dimerization systems have been recently developed to control signaling or cytoskeletal events in a spatiotemporally precise manner. We illustrate that, within minutes of global membrane recruitment of full-length GEFs or their catalytic domains only, widespread increases or decreases in F-actin rich protrusions and cell size occur, depending on the particular node in the networks targeted. Additionally, we demonstrate localized GEF recruitment as a robust assay system to study local network activation-driven changes in polarity and directed migration. Altogether, these optical tools confirmed GEFs of Ras superfamily GTPases as regulators of cell shape, actin dynamics, and polarity. Furthermore, this optogenetic toolbox may be exploited in perturbing complex signaling interactions in varied physiological contexts including mammalian embryogenesis.